Analysis of the possibility of, and challenges associated with, the qualification for refugee status of victims of human trafficking in South Africa - De Souza, Monica (2011)
Includes bibliographical references.The aim of the enquiry is to establish whether trafficking victims could find protection within a particular human rights framework - that of refugee law - and to assess any factors that may hinder qualification for such protection